Principals Distributed Leadership Practices and its’ Impact on Teaching and Learning in Type 1AB and Type 1C Schools in the Colombo District Sri Lanka - H. M. Lalitha Kumari (Researchparks Publishing, 2022)
Distributed leadership has been identified as one of the most important leadership practices in terms of enhancing quality of teaching and learning since it involves many members of the school. The main purpose of distributed leadership is to create secondary level leaders within the school and thus give more opportunities for teachers to improve their leadership skills. This study focused on investigating the distributed leadership practices and its impact on teaching and learning in type 1AB and type 1C schools in Sri Lanka. The objectives of this study were to identify how principals and teachers understand the concept of distributed leadership; how distributed leadership practices enhance teaching and learning; and what challenges principals and teachers face when devolving and practicing leadership responsibilities in their schools. Altogether 10 schools, 10 principals, 10 sectional heads and 200 teachers were selected for the study. Both questionnaires and semi-structured interviews were used to gather necessary data. The findings revealed that all the principals and a significant number of teachers in the type 1AB and type 1C schools fully understood the concept of distributed leadership and have linked with teaching and learning. The study further revealed that the distributed leadership practices contributed to enhance quality of teaching and learning in both types schools to some extent. However, it was revealed from this study that a significant number of teachers reluctant to undertake leadership responsibilities and hence principals in both types schools face challenges when devolving leadership responsibilities among the staff.